TRANSMISSION SYSTEM PROTOTYPE AS SPEED OPTIMIZATION IN THE POWER DRIVE MECHANISM OF THE MAKER S4000 MACHINE AT PT DM - Mahernanda Putanto, Christian Yokevin; Nugraha, Aditya; Nugroho, Yohanes; Karyadi, Bagus (Magister Teknik Mesin Universitas Pancasila, 2025)
The S4000 maker machine at PT DM faces issues during the cigarette rod cutting process due to a mismatch in speed between the servo motors in the feeding and cutting processes. This lack of synchronization results in imprecise cuts and an increase in defective products. This problem indicates the need for a system capable of mechanically synchronizing the rotational speeds between the two processes. This study aims to design a gear transmission system as a solution to synchronize the speeds between the feeding and cutting processes. Problem analysis was conducted using the Failure Mode and Effect Analysis (FMEA) method. The design process follows the VDI 2221 method, which includes functional requirement analysis, development of several conceptual alternatives, evaluation of transmission ratios, and selection of suitable mechanical components. Structural strength analysis was carried out through simulations using Finite Element Analysis (FEA). A system prototype was created using 3D printing as a design verification tool. The results show that the transmission system is capable of delivering synchronized rotation, resulting in consistent cigarette rod lengths. The FEA simulation indicates the system is safe under working loads. The prototype was successfully validated both visually and functionally, serving as a basis for evaluation prior to actual implementation